2014
DOI: 10.1007/s40732-014-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Relations in Stimulus Equivalence Classes of Preschool Children and Individuals with Down Syndrome

Abstract: We evaluated emergent stimulus-stimulus relations after two different training procedures. Participants were five typically developing preschool children and three individuals with Down Syndrome. Experiment 1 used two-comparison matching to sample (MTS) to establish AB and BC relations. Experiment 2 used two-comparison and blank-comparison MTS, each on 50% of training trials to establish AB and BC relations. In both experiments, tests for emergent relations (AC, CA) were conducted to assess equivalence class f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…What is particularly relevant for people with developmental disabilities, and for our study, is that they show more variability and difficulties in learning both baseline and derived stimulus relations, as expressed through the number of training trials required to master criteria and the accuracy during tests of equivalence (Grisante et al, 2014;O'Donnell & Saunders, 2003;Tovar & Westermann, 2017). Some authors have suggested that problems with deriving correct stimulus relations are correlated with poor language development (Devany et al, 1986).…”
Section: Introductionmentioning
confidence: 82%
“…What is particularly relevant for people with developmental disabilities, and for our study, is that they show more variability and difficulties in learning both baseline and derived stimulus relations, as expressed through the number of training trials required to master criteria and the accuracy during tests of equivalence (Grisante et al, 2014;O'Donnell & Saunders, 2003;Tovar & Westermann, 2017). Some authors have suggested that problems with deriving correct stimulus relations are correlated with poor language development (Devany et al, 1986).…”
Section: Introductionmentioning
confidence: 82%
“…All six participants formed equivalence classes with digital photos. Given the participants' ages (about 4 years old), equivalence class formation with digital photos might be expected based on previous research (e.g., Grisante, de Rose, & McIlvane, ). However, generalized equivalence responding had not been previously investigated in behavior analytic research with children of this age.…”
Section: Discussionmentioning
confidence: 99%
“…Had the pigeons done so (they did not), then the authors would have termed this outcome S‐delta control—a reject relation using more recent terminology. Most subsequent studies that have addressed select and/or reject controlling relations have adopted the “novel” stimulus substitution method (e.g., Grisante et al, 2014; Johnson & Sidman, 1993; Scienza et al, 2019; Stromer & Osborne, 1982), and most researchers seem to have followed the advice of Carrigan and Sidman (1992) who suggested the use of novel stimuli for purposes of testing for sample‐S‐ relations and potentially biasing participants toward their acquisition. However, other contemporaneous work (e.g., Dixon et al, 1983; McIlvane et al, 1984) pointed out that novel stimuli were not necessarily neutral in valence and could exhibit stimulus control properties that might render them unsuitable in conducting precise tests of select and reject controlling relations.…”
mentioning
confidence: 99%